SELF CORRECTION BY USING VOICE RECORDING TO ENHANCE PRONUNCIATION ON NARRATIVE ESSAY MONOLOG - hasbullah mpd (TIRAI EDUKASI: Jurnal Pendidikan, 2019)
The data gathered from the Report of Study and the Diagnostic Test results, which focus on specifically testing students’ pronunciation, showed that the speaking ability of second semester of medical record student Academic Year 2015/2016 was relatively low. Generally, the problems were students considered that English was difficult subject; they were diffident when they spoke English and teachers found difficulties in correcting students’ mispronunciation. Those were because they often forgot the corrected pronunciation and teachers required much of time to check or to correct each student’s mispronunciation as well. For those, the researcher conducted a classroom action research to enhance students’ pronunciation through self-correction using voice recording and to observe how the implementation of self-correction using voice recording can fix mispronunciation. The research resulted progresses on two cycles; 10.99% and 12.49%. Based on those results, there were improvements on students’ pronunciation and students showed positive response towards the use of self-correction using voice recording to enhance pronunciation.